2022-RA-1551-ESGO Impact of age on first line treatments of ovarian cancer and their outcomes: results from the Unicancer ESME OVR real-world database. (20th October 2022) - Lefevre, Leïla Bengrine; Fouquier, Anaïs; Ray-Coquard, Isabelle; Favier, Laure; Joly, Florence; Rodrigues, Manuel; Sauterey, Baptiste; Colombo, Pierre Emmanuel; Floquet, Anne; Leblanc, Eric; Sabatier, Rene; Barranger, Emmanuel; et al.
Abstract : Introduction/Background: Older patients with advanced ovarian cancer (AOC) have a poor survival. EWOC-1 study showed that carboplatin AUC5 monotherapy (C) was associated with 2.79-fold worse survival compared to carboplatin-paclitaxel (CP) combination in frail older patients. MITO7 study provided exploratory data in favor of weekly CP (wCP) compared to standard CP (sCP) in patients aged ≥70 years. A post hoc study on ICON7 database argued for a higher benefit of bevacizumab (Bev) in chemo-resistant tumors. Confirming the data in a real life database is fundamental to confirm results observed in randomized trials when exploration questioned the frailty. Methodology: On the Unicancer ESME-OVR national database (NCT03275298 ) were analyzed in patients in first line FIGO stages III-IV high grade AOC the impact of age, chemotherapy regimens and Bev exposure on overall survival. Results: 4686 patients were included, 888 had bevacizumab (≥70: 253); 2583 had sCP (≥70: 570); 171 had C (≥70: 150); 379 had weekly CP (≥70: 132). Median follow-up was 64.9 months, median OS 61.3 months (95%CI: 58.0–63.8). In patients aged ≥70, OS was 43.8 months (95%CI: 40.5–47.0), HR[≥70]: 1.74 (95%CI: 1.59–1.90), p <.001); C was associated with a worse outcome (reference: sCP): HR[C, ≥70]: 1.61 (95%CI: 1.29–2.00); HR[wCP, ≥70]: 0.96 (95%CI: 0.73–1.27), p ≤.001. In patients treated with sCP or wCP, the impact of older age persisted at a lesser extent: HR[≥70, sCP/wCP]: 1.64 (95%CI: 1.46–1.84), p<.0001. Bev tended to improve survival in older patients (HR[Bev, ≥70]: 0.80 (95%CI: 0.64–1.01), p =0.057), but not in younger patients (HR[Bev, <70]: 0.96 (95%CI: 0.84–1.10), p =0.596). Conclusion: In this real-world population, C was associated in univariate to a higher risk of death, confirming the conclusions of EWOC-1 trial. When considering sCP/wCP treatment, worse age impact persisted with a 1.64-fold risk of premature death. Bev tended to improve survival raising the possible role of chemo-resistance in the poorer outcome of older patients.